Development of Website for Public Relations Tourism in the Royal Temples in Nonthaburi Province - Khamtrong, Samornsri; Dheeranoot, Prukpoom (Journal of Humanities and Social Sciences, Rajapruk University, 2025)
The objective of this research article was to develop a website for public relations for the royal temples in Nonthaburi Province and to evaluate the developed website. The sample consisted of 6 content and web design experts, as well as 62 users who completed an online satisfaction survey. The tools used in this study were content and web design quality assessment forms, and satisfaction assessment forms for the website. The statistics used for data analysis were mean and standard deviation. The research results found that the website for public relations about royal temples in Nonthaburi Province was rated at a high quality level for content, with an average score of 4.96 and a standard deviation of 0.08; for web design, with an average score of 4.65 and a standard deviation of 0.42; and for user satisfaction, with an average score of 4.65 and a standard deviation of 0.52.